EFL Speaking Strategies For An Ecuadorian University Hotel Management And Tou. Risn Program - Cevallos Lecaro, Catalina Noemi (2016)
I have thirteen years teaching english in an ecuadorian university, and the last five years, i have been teaching english at the hotel management and tourism program at the same ecuadorian university. As an english instructor of the hotel management & tourism program, i observed that it was difficult for my students to feel confident to join a conversation in english. as the time passed by, i noticed that these students had production obstacles due to nervousness and lack of confidence.Moreover, these students looked for specific words and were not able to use simple language to communicate their ideas. Finally, these students were not skilful enough to communicate with a varied group of individuals (partners, bosses, teachers, administrators, etc). My interest in conducting research on teaching speaking strategies aroused just from those previous experiences. Being a witness of my students‟ speaking problems, made me reflect that i could not be a passive instructor.